Community Interaction with Moluccan Cockatoo (Cacatua moluccensis, Gmelin 1788) in The Buffer Zone of Manusela National Parks - Iyat Sudrajat; Harnios Arief; Tutut Sunarminto (Media Konservasi, 2019)
Moluccan cockatoo (Cacatua moluccensis Gmelin, 1788) is an endemic bird of Seram Island, Maluku Province, which is an icon of Manusela National Park. The population and habitat of Maluku cockatoos is disrupted by the activities of communities around the area. This study aims to analyze the condition of the poor cockatoo population and habitat as well as the community's perceptions of the interaction between the community and the cockatoos in the wild and develop a strategy for the Maluku cockatoo conservation program in the buffer zone of Manusela National Park.. Data collection is done by direct observation, questionnaires, focus group discussions and in-depth interviews. The results showed that there were 7 individuals found in the location of community plantations, while 4 other individuals were in the protected forest area and Manusela National Park with density 22,04 individual/km2. The existence of moluccan cockatoos on community plantations has led to a negative perception of the community that cockatoo is one of the pests for the plantation. The right conservation efforts to preserve cockatoos and create positive interactions with the community are by planning on village tourism, Moluccan cockatoo captivity, and managing the habitat of the cockatoos in and around the Manusela National Park area. Keywords: captivity, conservation, ecotourism, habitat, moluccan cockatoo